Radiological anatomy for FRCR. Part 1 - Borg, Philip; Alvi, Abdul Rahman; SpringerLink (Online service). (Dordrecht New York Springer-Verlag, 2011)
The new FRCR part 1 Anatomy examination comprises 20 cases/images, with five questions about each. The cases are labelled 01 to 20 and the five questions are labelled (a) to (e). The authors have set out to emulate this format by gathering 200 cases which, from their experience, are representative of the cases on which candidates will be tested. The book consists of 10 tests with 20 cases each, and 5 stem questions each. The answers, along with an explanation and tips, accompany each test at the end of the chapter. This will help candidates to identify the level of anatomical knowledge expecte.
Radiological Anatomy for FRCR Part 1; Foreword; Preface; Contents; Contributors; 1: Test; 2: Test; 3: Test; 4: Test; 5: Test; 6: Test; 7: Test; 8: Test; 9: Test 9: Paediatric Cases; 10: Chapter 10: Normal Anatomical Variants.
Electronic reproduction.
Keywords: Medical radiology -- Examinations, questions, etc; Anatomy -- education; Technology, Radiologic -- education; Electronic books